The wild party - Lippa, Andrew (Hal Leonard Distributed in the United States by BMG Distribution, 1999)
Out of the blue -- Raise the roof -- Look at me now -- Poor child -- An old-fashioned love story -- A wild, wild party -- Maybe I like it this way -- What is it about her? -- The life of the party -- I'll be here -- Let me drown -- How did we come to this?